Dynamic changes in CD4⁺ CD25⁺ high T cell apoptosis after the diagnosis of type 1 diabetes - Glisic-Milosavljevic, S; Wang, T; Koppen, M; Kramer, J; Ehlenbach, S; Waukau, J; Jailwala, P; Jana, S; Alemzadeh, R; Ghosh, S (Clinical and experimental immunology, 2007)
Because type 1 diabetes (T1D) is a chronic, autoimmune, T cell-mediated disease, interventions affecting T cells are expected to modulate the immune cascade and lead to disease remission. We propose that increased CD4⁺ CD25⁺high T cell apoptosis, a trait we discovered in recent-onset T1D subjects, reflects T1D partial remission within the first 6 months after diagnosis. Apoptosis of forkhead box P3 (FoxP3)⁺ CD4⁺ CD25⁺high T cells, in addition to total daily doses of insulin (TDD), blood glucose, HbA1c and age, were measured in 45 subjects with T1D at various times after diagnosis. Sixteen healthy control subjects were also recruited to the study. Higher CD4⁺ CD25⁺high T cell apoptosis levels were detected within the first 6 months of diagnosis (odds ratio = 1·39, P = 0·009), after adjustment for age, TDD and HbA1c. A proportional hazards model confirmed that the decline of apoptosis after diagnosis of T1D was related significantly to survival time (hazards ratio = 1·08, P = 0·014), with TDD and age also contributing to survival. During this time there was an inverse relationship between CD4⁺ CD25⁺high T cell apoptosis with TDD (r = -0·39, P = 0·008). The CD4⁺ CD25⁺high T cell apoptosis levels decline significantly after the first 6 months from diagnosis of T1D and may help in the close monitoring of autoimmunity. In parallel, there is an increase in TDD during this time. We also propose that CD4⁺ CD25⁺high T cell apoptosis assay can be used to gauge the efficacy of the several immune tolerance induction protocols, now under way.